Tari Kreasi Wija Prakerti - -, Ni Kadek Deviani; Wimba Ruspawati, Ida Ayu; Oka Adnyana, A.A. Ketut (Jurnal IGEL : Journal Of Dance, 2024)
The Wija Prakerti Dance is a new dance creation inspired by the story of therejang slahsah dance, namely the sacred rejang dance which is intended as a formof gratitude for the rice plant. The Wija Prakerti Dance tells the story of rice farmerswho are active in the rice fields. The Wija Prakerti Dance was created as a thankyou to the farmers. paddy.In the creation process, the creator collaborated with Sanggar Warini in theindependent campus learning program by taking independent studyprograms/projects. The creation of the Wija Prakerti Dance uses the AngriptaSasolahan creation method (creating dances) by I Kt. Suteja in the book CaturDormitory, the Spiritual Climbing of Balinese People in a Dance Work. The bookexplains the five stages of creation, namely planning, nuasen, makalin, nelesin, andngebah.The Wija Prakerti dance is a creative dance performed as a group with adance structure, namely pepeson, pengawak, pecet, pekaad, which lasts 11minutes. The creator hopes that the values contained in this work can conveygratitude to rice plants and gratitude to rice farmers.